Validity and reliability of sleep promotion questionnaire and predictors of quality of care. (August 2018) - Kim, Son Chae; Pedersen, Chase; Yi, Cassia
Background: Sleep disturbance is common among hospitalized patients. However, sleep promotion is not a high priority for most healthcare providers, which potentially impacts quality of care. Due to a paucity of validated tools to assess sleep promotion, little is known about the relationship between sleep promotion and quality of care. This study was conducted to assess the validity and reliability of a newly-developed instrument, the Sleep Promotion Questionnaire, and to examine sleep promotion as a predictor of quality of care. The Sleep Promotion Questionnaire includes dimensions of attitude, control, unit norms, intention, and behavior that are associated with sleep promotion. Methods: A total of 302 nurses participated in an online survey. The survey included the initial 36-item Sleep Promotion Questionnaire, a quality of care question, Caring Behavior Inventory, and Professional Quality of Life scale. An exploratory factor analysis was performed to determine the factor structure of the Sleep Promotion Questionnaire. The internal consistency reliability as well as the convergent and divergent validities was assessed. Pearson's correlations and hierarchical multiple regression procedures were performed to explore the predictors of perceived quality of care. Results: Exploratory factor analysis of the Sleep Promotion Questionnaire yielded 28 items in five subscales, comprising Attitude, Control, Unit Norms, Sleep-aid Intention, and Behavior. Convergent and divergent validities were supported ( r = 0.37; r = −0.38, respectively). The Cronbach's alphas of internal consistency reliabilities of the Sleep Promotion Questionnaire subscales ranged from 0.70 to 0.89. Regression models showed that sleep-promoting Unit Norms was the only significant predictor of perceived quality of care among both ICU and non-ICU nurses ( β = 0.40; β = 0.28, respectively). Conclusion: The Sleep Promotion Questionnaire appears to be a reliable and valid instrument with satisfactory psychometric properties for assessing sleep promotion, and it seems that having unit norms conducive to sleep promotion may positively impact the quality of care. However, further studies are needed to confirm these results.